Vehicle Dynamics Management - Benefits of Integrated Control of Active Brake, Active Steering and Active Suspension Systems - Verhagen, Armin; Futterer, Sylvia; Rupprecht, Josef; Trächtler, Ansgar (Proc. FISITA)

Mapping High Quality Textures on an Interactive Globe - Goetz, F.; Boenning, B.; Domik, Gitta (Proc. of The 4th IASTED International Conference on Visualization, Imgaging, and Image Processing)

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Systematic mistuning of bladed disk assemblies with friction contacts - Götting, Florian; Sextro, Walter; Panning, Lars; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
In turbomachinery, friction contacts are widely used to reduce dynamic stresses in turbine blades in order to avoid expensive damages. As a result of energy dissipation in the friction contacts the blade vibration amplitudes are reduced. In case of so-called friction dampers, which are pressed on the platforms of the blades by centrifugal forces, the damping effect can be optimized by varying the damper mass. This optimization can be done by means of a simulation model applying the so-called component mode synthesis and the Harmonic Balance Method to reduce computation time. It is based on the modal description of each substructure. In a real turbine or compressor blading great differences in the magnitude of the individual blade amplitudes occur caused by unavoidable mistuning of all system parameters like contact parameters and natural frequencies of the blades. It may happen that most of the blades experience only small stresses whereas a few blades experience critical stresses. Therefore, it is necessary to consider mistuning for all system parameters to simulate the forced response of bladed disk assemblies with friction contacts. For a mistuned bladed disk the complete system has to be modeled to calculate the dynamic response. In practice, usually the standard deviations instead of the distributions of the system parameters are known. Therefore, Monte-Carlo simulations are necessary to calculate the forced response of the blades for given mean values and standard deviations of the system parameters. To reduce the computational time, an approximate method has been developed and extended for small and moderate standard deviations of the system parameters to calculate the distribution and the envelopes of the frequency response functions for statistically varying system parameters, in the following called statistical mistuning. The approximate method is based on a sensitivity analysis and the assumption of a Weibull distribution of the vibration amplitudes of the blades. Both, the approximate method and the assumption of a Weibull distribution of the vibration amplitudes are validated by Monte-Carlo simulations. By these investigations the influence of different arrangements of the system parameters for given mean values and standard deviations of the vibration amplitudes of the blades can be determined, too. For the present investigations only a small influence of the arrangement of blades with respect to their natural frequencies has been observed. On the other hand, an intentional mistuning of the damper masses and the natural frequencies of the blades in a systematic way, in the following called systematic mistuning, can be investigated to reduce the amplitudes of the system. The simulation results of a systematic mistuning has been validated by a test rig with a rotating bladed disk assembly with friction dampers. The investigations show a good agreement between the simulations and the measurements but only a slight decrease of the maximum amplitudes in case of a systematic mistuning. Copyright {©} 2004 by ASME
Keywords: Friction; Disks

Linear piezoelectric motors and their application - Hemsel, Tobias (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

A novel approach for high power ultrasonic linear motors - Hemsel, Tobias; Mracek, Maik; Wallaschek, Jörg; Vasiljev, Piotr (Ultrasonics Symposium, 2004 IEEE)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable e.g. to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: the electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well organized and controlled to get an optimized drive that is not oversized and costly.
Keywords: drives; electromechanical effects; linear motors; ultrasonic motors; car sunroof; car window; electromechanical behavior; high power ultrasonic linear motors; multiple miniaturized motors; positioning tasks; translatory drive; Costs; Electromagnetic forces; Frequency; Laboratories; Manufacturing; Mechatronics; Micromotors; Ultrasonic imaging; Vibrations; Voltage

Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Design criteria for piezoelectric transformers - Littmann, Walter; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics)

Self configuration of miniature ultrasonic linear motors - Mracek, Maik; Wallaschek, Jörg; Hemsel, Tobias (Proceedings of the 18th International Congress on Acoustics)

Asymmetrical Underplatform Dampers in Gas Turbine Bladings: Theory and Application - Panning, Lars; Popp, Karl; Sextro, Walter; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
During operation, the rotating blades of a gas turbine are subjected to centrifugal forces as well as fluctuating gas forces, resulting in blade vibrations. In addition to material damping, aerodynamical and blade root damping, underplatform dampers are widely used to increase the amount of damping and to decrease blade vibration amplitudes. The friction forces generated by the relative displacements between the underplatform damper and the blade platforms provide a significant amount of energy dissipation. In practice, a number of different underplatform damper designs are applied. Basically, these are wedge dampers with flat contact areas, cylindrical dampers with curved surfaces or asymmetrical dampers with both flat contact surfaces on one side and curved contact surfaces on the other. The latter damper type combines the advantages of both the wedge and the cylindrical damper by preventing the damper from pure rolling on the one hand as it has been observed for cylindrical dampers and on the other hand, avoiding a diverged plane area contact in case of a wedge damper, causing a damper lift-off. This paper will focus on the investigation of cylindrical and asymmetrical underplatform dampers. A comparison between measurements of rotating assemblies in Siemens PG gas turbines (V84.2, V64.3A and V94.3A(2)) under test and real operating conditions with cylindrical and asymmetrical underplatform dampers and the predictions of the developed theoretical model are presented. Special attention is paid to the frequency shift due to the application of an underplatform damper, since in particular for stationary gas turbines, in addition to the amplitude reduction, the accurate prediction of the resonance frequency is of major interest. Copyright {©} 2004 by ASME
Keywords: Dampers; Gas turbines

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Proceedings of "DeLFI 2004: Die 2. e-Learning Fachtagung Informatik", Paderborn (Germany)

Modeling and Development of Multimedia Systems

Proceedings of the 2nd International Conference on Graph Transformations (ICGT 2004), Rome (Italy)

Peer-To-Peer Technology for Interconnecting Web Services in Heterogeneous Networks - Schattkowsky, Tim; Loeser, Christoph; Müller, Wolfgang (Proceedings of the 18th International Conference on Advanced Information Networking and Applications (AINA 2004), Fukuoka (Japan))

Style-Based Refinement of Dynamic Software Architectures - Baresi, Luciano; Heckel, Reiko; Thöne, Sebastian; Varró, Dániel (Proceedings of the conference on Software Architecture (WICSA 2004), Oslo (Norway))

Software Testing via Model Checking - Belli, Fevzi; Güldali, Baris (Proceedings of the conference on Computer and Information Sciences (ISCIS 2004), Kemer-Antalya (Turkey))

Conceptual Modeling of Styles For Mobile Systems: A layered approach based on graph transformation - Heckel, Reiko; Guo, Ping (Proceedings of the conference on Mobile Information Systems (MOBIS 2004), Oslo (Norway))

Application of Graph Transformation for Automating Web Service Discovery - Heckel, Reiko; Cherchago, Alexey (Proceedings of the seminar on Language Engineering for Model-Driven Software Development (2003), Dagstuhl (Germany))

Model-Based Design of Embedded Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of the 7th IEEE International Symposium on Object-Oriented Real-Time Distributed Computing (ISORC 2004), Vienna (Austria))